The Current Crisis of the South African Labour Movement - Rachleff, Peter (Labour / Le Travail, 2001)
[The article focuses] on a particular conflict in South Africa — the strike this past winter of several thousand Volkswagen workers in Uitenhage, outside of Port Elizabeth, a region known as "the Detroit of South Africa" — and [places] it within the context of a worsening material situation for most South Africans and growing political contusion and tension within the ruling "Triple Alliance" of the African National Congress (ANC), the Confederation of South African Trade Unions (COSATU), and the South African Communist Party (SACP). At this moment, there is an intensifying struggle over privatization and restructuring, a pending battle between pubhc employees and the ANC-run state; and growing enmity between COSATU and the ANC, driven by dissent within COSATU affiliates, over these issues of privatization, the pay of public employees, and a call for the revisions of labour laws in place since 1994, These particular conflicts and the overall situation rest, of course, on South Africa's location within the global economy and the different ways that internal forces are responding to it. In examining these internal forces we can learn more about not only the challenges of economic globalization but also the prospects for challenging it. --From author's introduction